Toward a Quantification of the Effects of Microsoft's Conduct - Hall, Chris E; Hall, Robert E (American Economic Review, 2000)
Microsoft stands accused of an illegal defense of its dominant position in the desktop operatingsystem market. According to the charge, exclusionary contracts and predatory conduct dealing primarily with the Internet browser prevented the browser from evolving into a rival for Microsoft’s operating system, Windows. Earlier, the government negotiated a consent decree with Microsoft limiting exclusionary terms in the company’s contracts with computer makers. Our purpose here is to investigate quantification of the effects of the challenged conduct. By how much will the computer purchaser gain from the elimination of artificial barriers to entry in the operating-system business? Or, to put the question the other way around, how much harm did the conduct cause before it was brought under control? We also discuss policies for controlling artificial barriers. A related more detailed paper, Hall (1999), develops a model to deal with these issues at a more general level. Here we will present a stripped-down version of the model and apply it to Microsoft.